Conformity and reactions to deviance in the time of COVID-19. (February 2021) - Packer, Dominic J.; Ungson, Nick D.; Marsh, Jessecae K.
We have seen massive global behavioral change as billions of people radically altered their ways of life in response to COVID-19. Here, we review how research on conformity and deviance can inform understanding of and effective responses to the pandemic. Group identities are critical for understanding who is influenced by whom, as well as how partisan divisions can obstruct cohesive and coordinated action. We identify several questions highlighted by the pandemic, including when people will react more harshly to ingroup members who violate health-protective norms (black sheep effect) or to outgroup members violating the same norms (intergroup hypocrisy). As a working hypothesis, we propose a goal-based approach, positing that differentially negative reactions to ingroup and outgroup deviants are likely influenced by the relative salience of goals to protect ingroup image, enforce group norms, maintain intergroup boundaries, and seek justice for potential victims put at risk by norm-violating behavior.